A Study the Brain Tumor detection by using Artificial Neural Networksand Classification of Brain Tumors: The Importance of Early Detection in Brain Tumor Diagnosis (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Brain tumor is a life threatening disease and its early detection is very important to save life. Abrain tumor is an abnormal collection of cells that forms in the brain. Tumors of the brain are referred toby their place of origin, the brain. Tumors are masses of abnormal tissue that develop inside the skull asa result of unchecked cell division. Brain tumors may also develop as a result of metastasis from canceroriginating in other parts of the body. In cases when tumors are located in the posterior fossa of theskull, the largest ones tend to be found in the cerebral hemispheres. Some brain tumors are harmlesswhile others are malignant. Tissue involvement, tumor location, and other factors all play a role in thecategorization process. Brain MRI segmentation can be utilized to find the tumor region. Systems formedical imaging are essential for getting images of the human body.